Guillaume-Benjamin Duchenne: a miserable life dedicated to science - Péricles MARANHÃO-FILHO; Maurice VINCENT (Arquivos de Neuro-Psiquiatria)
ABSTRACT Duchenne de Boulogne is known mainly by the disease eponymously named “Duchenne muscular dystrophy”, or pseudohypertrophic muscular dystrophy, although some experts consider that the original description of this disease does not belong to him. Less well known are the facts related to the tragic death of his beloved wife shortly after the birth of his only child, the unjustifiable distance he was forced to keep from this son for more than 30 years, and of being humiliated and professionally despised by his peers. These events made the life of this physician, physiologist, researcher and inventor extremely arduous. We emphasize some aspects of the history of this man, his work and his life, a true genius of few friends.